Methylation changes in the peripheral blood of Filipinos with type 2 diabetes suggest spurious transcription initiation at TXNIP - Albao, Dominic S.; Cutiongco-de la Paz, Eva Maria; Mercado, Maria Elizabeth; Lirio, Alvin; Mariano, Margarette; Kim, Sarah; Yangco, Ariane; Melegrito, Jodelyn; Wad-asen, Kate; Gauran, Iris Ivy; Francisco, Marie Angeline; Santos-Acuin, Cecilia; et al. (Oxford University Press, 2019)
While much work has been done in associating differentially methylated positions (DMPs) to type 2 diabetes (T2D) across different populations, not much attention has been placed on identifying its possible functional consequences. We explored methylation changes in the peripheral blood of Filipinos with T2D and identified 177 associated DMPs. Most of these DMPs were associated with genes involved in metabolism, inflammation and the cell cycle. Three of these DMPs map to the TXNIP gene body, replicating previous findings from epigenome-wide association studies (EWAS) of T2D. The TXNIP downmethylation coincided with increased transcription at the 3’-UTR, H3K36me3 histone markings, and Sp1 binding, suggesting spurious transcription initiation at the TXNIP 3’-UTR as a functional consequence of T2D methylation changes. We also explored potential epigenetic determinants to increased incidence of T2D in Filipino immigrants in the United States and found 3 DMPs associated with the interaction of T2D and immigration. Two of these DMPs were located near MAP 2 K7 and PRMT1, which may point towards dysregulated stress response and inflammation as a contributing factor to T2D among Filipino immigrants.